2013
DOI: 10.3384/diss.diva-99786
|View full text |Cite
|
Sign up to set email alerts
|

Representing sounds and spellings: Phonological decline and compensatory working memory in acquired hearing impairment

Abstract: Representing sounds and spellingsPhonological decline and compensatory working memory in acquired hearing impairment Pursue one great decisive aim with force and determination.Carl von Clausewitz "On war" AbstractLong-term severe acquired hearing impairment (HI) is associated with a deterioration of phonological representations in semantic long-term memory that negatively affects phonological awareness (Andersson, 2002). The primary aim of this thesis was twofold: to use electrophysiological and behavioral mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 217 publications
(442 reference statements)
0
6
0
Order By: Relevance
“…Most studies have defined their criteria for categorizing low vs. high working memory groups according to the mean or median of the test group, with criterion scores ranging from 36% to 44% correct (Classon, 2013). For this study, participants with scores less than or equal to 41% correct were categorized as having low working memory.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have defined their criteria for categorizing low vs. high working memory groups according to the mean or median of the test group, with criterion scores ranging from 36% to 44% correct (Classon, 2013). For this study, participants with scores less than or equal to 41% correct were categorized as having low working memory.…”
Section: Methodsmentioning
confidence: 99%
“…For this study, participants with scores less than or equal to 41% correct were categorized as having low working memory. The 41% criterion was based on a review of several previous datasets with greater weight given to larger datasets (e.g., Souza & Arehart, 2015; Arehart, Souza, Baca & Kates, 2013; Classon, 2013). Based on this criterion, nine participants were categorized as having high working memory (mean scores 47.5% correct, range from 43.0% to 50% correct).…”
Section: Methodsmentioning
confidence: 99%
“…However, there seems to be no differences in mean performance between the two test versions (Classon, 2013). …”
mentioning
confidence: 90%
“…For example, a relationship between severe to profound HL and deficiency in certain aspects of phonological processing has been demonstrated and suggested to come from a gradual loss of specificity of phonological representations (Andersson, 2002;Andersson & Lyxell 1999;Lyxell, Andersson, Borg, & Ohlson 2003;Rönnberg et al, 2011;Classon, 2013). Andersson (2002) concluded that specific aspects of the phonological system deteriorate in the HL population as a function of auditory deprivation.…”
Section: Cognitive Consequences Of Hlmentioning
confidence: 99%